Hubungan antara Disisplin Belajar dan Motivasi Belajar dengan Hasil Belajar PPKn Siswa SDN se-Kecamatan Banjarnegara Tahun Ajaran 2021/2022 - Rachma Mutiara Dewi; Muhammad Chamdani; Ngatman Ngatman (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2022)
AbstractThe study aimed to prove that there was the positive correlation between learning discipline and learning motivation on Pancasila and Civic Education learning outcomes to fourth grade students of public elementary schools in Banjarnegara Sub-district in academic year of 2021/2022. The population were 804 fourth grade students and the samples were 363 fourth grade students. Data collection techniques used questionnaires and tests. The validity method included question analysis using Pearson correlation analysis. Reliability used the Alpha (Cronbach’s) formula. The prerequisite test used normality test, linearity test, and multicollinearity test. Data analysis techniques used multiple correlation analysis. The result indicated that the correlation value between learning discipline and learning motivation was 0.570 on Pancasila and Civic Education learning outcomes. The significant value was 0.000 less than 0.5.